The Behavior of Using Digital Money (E-Money) in the Millennial Generation Based on Islamic Perspective - Zuhriyah, Qurrotul Aini (HM Publisher, 2022)
OVO digital money is a means of payment in electronic form where the value of money is stored in certain electronic media. Users must first deposit their money to the publisher and store it in electronic media before using it for transaction purposes. Currently, there are two types of digital money in Indonesia, namely server-based digital money and chip-based digital money. This study aims to describe the behavior of using digital money in the millennial generation and its review based on Islamic perspective. This research is an observational study with a qualitative approach. Data were collected by interview, observation, and documentation methods. Data analysis was done descriptively. The results of the study show that forms of digital money transactions (OVO) are used as a means of payment for retail transactions, payments for online transportation orders and food orders, payments in e-commerce, and are used to pay bills such as purchasing credit or data packages. Muslim consumer behavior at IAIN Kediri students in using OVO is still in the reasonable stage and not excessive. In conclusion, IAIN Kediri students have shown the use of e-money based on Islamic perspective, namely shopping as a need, not as a desire, consuming halal goods, and not spending excessively.